Barriers to preventive actions in oral health perceived by pregnant women in Monteria, Colombia - De Arco-Montiel, Sarita; Valencia-Jiménez, Nydia Nina (Universidad y Salud, 2023)
Introduction: The low effectiveness of programs for the promotion and maintenance of oral health in pregnant women is caused by various barriers. Objective: To understand the barriers perceived by pregnant women from Monteria (Colombia) for the application of preventive behaviors in oral health. Materials and methods: A qualitative micro-ethnographic study that applied direct observation, field diary, and in-depth interviews to 19 pregnant women from section 4 of Monteria, Colombia. Results: The main barrier for pregnant women was fear to request dental care. Dental cavities and loss due to pregnancy, perception of fear of the treating dentist as well as the precariousness of the dental care service were the reasons why pregnant women used home practices as dental alternatives to mitigate oral conditions. Conclusions: Barriers experienced by pregnant women may be the cause of the inefficiency of the health promotion programs aimed at them. Therefore, maternal health care teams must work together in order to recognize them as active participants and learn how to minimize health-risk beliefs and attitudes.